Konsumsi Minuman Berpemanis pada Siswa Menengah Pertama - Adelia, Gita; Tampubolon, Sri Devi Liliyani; Azhar, Bayu; Putri, Veni Dayu (REAL in Nursing Journal, 2024)
Background: Globally, adolescents are one of the largest consumers of sugar-sweetened beverages with a prevalence of 72%. This study aims to analyze the picture of sweetened beverage consumption among adolescents in SMP Negeri 6 Pekanbaru. Methods: This descriptive study involved 86 junior high school students. The questionnaires used were Food Frequency Questionnaire (FFQ) and Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Results: The results found that more than half were male (55.8%), with an average age of 13.48 years in the age range (13-14 years). The type of sugar-sweetened beverage consumed with the highest average is Flavored milk, which is 4.32 (2-5) and the least consumed is the type of Energy drink as much as 0.33 (0-2). Almost all respondents consumed sugar-sweetened beverages (≥3 times/week at (98.84%) or in the high category and more than half of the respondents consumed sugar-sweetened beverages more than> 50 g/day (58.1%).Conclusion: This high consumption of sweetened drinks indicates the need for more intensive nursing interventions to educate adolescents and their families about the importance of healthy eating patterns and the long-term impacts of consuming sweetened drinks.